Lethal experimental infections of rhesus monkeys by aerosolized Ebola virus. - Johnson, E. (1995)
The potential of aerogenic infection by Ebola virus was established by using a head-only exposure aerosol system. Virus-containing droplets of 0.8-1.2 microns were generated and administered into the respiratory tract of rhesus monkeys via inhalation. Inhalation of viral doses as low as 400 plaque-forming units of virus caused a rapidly fatal disease in 4-5 days. The illness was clinically identical to that reported for parenteral virus inoculation, except for the occurrence of subcutaneous and venipuncture site bleeding and serosanguineous nasal discharge. Immunocytochemistry revealed cell-associated Ebola virus antigens present in airway epithelium, alveolar pneumocytes, and macrophages in the lung and pulmonary lymph nodes; extracellular antigen was present on mucosal surfaces of the nose, oropharynx and airways. Aggregates of characteristic filamentous virus were present within type I pneumocytes, macrophages, and air spaces of the lung by electron microscopy. Demonstration of fatal aerosol transmission of this virus in monkeys reinforces the importance of taking appropriate precautions to prevent its potential aerosol transmission to humans.